2009
DOI: 10.1183/09031936.00047709
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of nasal continuous positive airway pressure on insulin sensitivity in obstructive sleep apnoea

Abstract: The effects of treatment of obstructive sleep apnoea (OSA) on glucose metabolism have been investigated previously with conflicting results. This study evaluated the impact of nasal continuous positive airway pressure (nCPAP) treatment of OSA on insulin sensitivity.Males with moderate/severe OSA and no significant comorbidity were randomised to a therapeutic or sham nCPAP treatment group for 1 week and then reassessed. Those who received therapeutic nCPAP were further evaluated at 12 weeks. Insulin sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
128
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(139 citation statements)
references
References 40 publications
6
128
0
5
Order By: Relevance
“…estimated by the short insulin tolerance test in Asian men with no diabetes (30). In our study, the participants used CPAP continuously (except for rare bathroom breaks) in the laboratory during the entire duration of the time in bed (i.e., from 11:00 P.M. to 7:00 A.M.), which is comparable with approximately 8 hours of nightly objective CPAP adherence downloaded from devices in a clinical setting.…”
Section: Original Articlesupporting
confidence: 49%
See 2 more Smart Citations
“…estimated by the short insulin tolerance test in Asian men with no diabetes (30). In our study, the participants used CPAP continuously (except for rare bathroom breaks) in the laboratory during the entire duration of the time in bed (i.e., from 11:00 P.M. to 7:00 A.M.), which is comparable with approximately 8 hours of nightly objective CPAP adherence downloaded from devices in a clinical setting.…”
Section: Original Articlesupporting
confidence: 49%
“…First, because air pressure is the mechanism of action of CPAP, sham devices may feel different due to a markedly lower mask air pressure compared with the therapeutic device, which may adversely affect its tolerability and acceptance by patients. Indeed, several studies investigating the effects of CPAP on glucose metabolism have reported lower average duration of sham-CPAP adherence as compared with therapeutic CPAP (20,21,29,30). A large randomized controlled multicenter trial (56), comparing the effects of therapeutic versus sham-CPAP, reported significantly lower adherence to sham-CPAP and a lower retention rate in the sham-CPAP group.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…U ntreated obstructive sleep apnea (OSA) is associated with insulin resistance, 1,2 and some studies suggest that treatment with CPAP improves glucose control, 3,4 although this was not found in a randomized controlled trial of diabetics with sleep apnea. 5 The observation that established type 2 diabetics cannot improve glucose control when their OSA is treated with CPAP, emphasizes the importance of understanding the pathophysiology of insulin resistance associated with OSA.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…Hypoxia has been shown to induce a multitude of Dawson et al [49] Type 2 diabetes with OSA [52] OSA and metabolic syndrome 20 None Fasting blood glucose 1 yr No difference in blood glucose seen _ Lam et al [53] OSA patients 61 (30 control and 31 study group)…”
Section: Pathophysiologymentioning
confidence: 99%